Of monsters in men ideology behind environmental policy - Caldona, Enrico C. (Philippine Law Journal, 2023)
Environmental policy is divided. The West is mainly concerned with people's injuries and rights, employing anthropocentric approaches. On the other hand, the Global South pushes for the environment's legal personhood. This paper argues that both sides are similarly incomplete and inadequate to address the crux of environmental issues: the systemic denial of the abuse of the environment. Both sides focus only on man's perspectives, ignore the environment's perspective, and only talk about what the environment means to man without considering what man means to the environment. Exemplified in the Philippines, Resident Mammals v. Reyes on environmental legal standing, among other recent environmental jurisprudence, reveals an anthropocentric framework focusing on environmental rights from which duties are merely derived. However, to frame policy only in terms of rights would be a linear and myopic view of the history of injustice man has perpetrated on the environment. Thus, to address this gap, environmental policy should instead be grounded on the enforcement of such duties. In other words, all people have legal standing because they have the duty to respect the environment by enforcing environmental laws. Applied in the Philippines, man's duties to the environment should be constitutionally enshrined independently from the right to a balanced and healthful ecology to make such duties a matter of State policy.